Evaluation of Ralgro® on pasture and subsequent feedlot performance and carcass merit of Mexican crossbred steers - S.I. Paisley; Gerry L. Kuhl; James J. Higgins; G.L. Huck; T.B. Farran; J.J. Sindt; Sean P. Montgomery; C. Birkelo; Dale A. Blasi; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2001)
A pasture/feedlot field study was conducted to evaluate the effects of a single Ralgro® implant during the stocker phase on steer grazing performance and subsequent feedlot performance and carcass merit. A total of 2,764 steers of Mexican origin averaging 449 lb were assembled in Texas and shipped to Kansas, where they grazed on three intensively-early-stocked Flint Hills pastures. At initial processing, the steers were individually weighed and randomly assigned to either a non-implanted control group or a Ralgro implant group. Ralgro steers gained more (23 lb; P<0.01) than controls during the 82- to 93-day grazing phase. Following the grazing phase, all steers were shipped to a commercial feedlot in southwestern Kansas where steers from each pasture were individually weighed and given a single Component E-S® implant. Immediately after processing, steers from each pasture were sorted into either a light- or heavy-weight pen, regardless of pasture implant treatment, resulting in six feedlot pens. Days on feed ranged from 127 to 197. Control steers gained faster (P<0.01) during the feedlot phase; however, Ralgro steers had higher cumulative weight gains across the combined pasture and feedlot phases (P<0.01) and averaged three fewer days on feed (P<0.05). There were no significant differences for marbling, fat thickness, ribeye area, KPH fat, or yield grade. Ralgro steers had lower (P<0.05) quality grades because of a higher incidence (P<0.001) of steers with B and C carcass maturities.
Keywords: Cattlemen' s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Growth implant; Ralgro; Steers; Pasture; Feedlot; Carcass traits